Physiological responses during ascent to high altitude and the incidence of acute mountain sickness. Issue 7 (27th April 2021) - Cobb, Alexandra B.; Levett, Denny Z. H.; Mitchell, Kay; Aveling, Wynne; Hurlbut, Daniel; Gilbert‐Kawai, Edward; Hennis, Philip J.; Mythen, Monty G.; Grocott, Michael P. W.; Martin, Daniel S.
Abstract: Acute mountain sickness (AMS) occurs when there is failure of acclimatisation to high altitude. The aim of this study was to describe the relationship between physiological variables and the incidence of AMS during ascent to 5300 m. A total of 332 lowland‐dwelling volunteers followed an identical ascent profile on staggered treks. Self‐reported symptoms of AMS were recorded daily using the Lake Louise score (mild 3–4; moderate‐severe ≥5), alongside measurements of physiological variables (heart rate, respiratory rate (RR), peripheral oxygen saturation (SpO2 ) and blood pressure) before and after a standardised Xtreme Everest Step‐Test (XEST). The overall occurrence of AMS among participants was 73.5% (23.2% mild, 50.3% moderate–severe). There was no difference in gender, age, previous AMS, weight or body mass index between participants who developed AMS and those who did not. Participants who had not previously ascended >5000 m were more likely to get moderate‐to‐severe AMS. Participants who suffered moderate‐to‐severe AMS had a lower resting SpO2 at 3500 m (88.5 vs. 89.6%, p  = 0.02), while participants who suffered mild or moderate‐to‐severe AMS had a lower end‐exercise SpO2 at 3500 m (82.2 vs. 83.8%, p  = 0.027; 81.5 vs. 83.8%, p  < 0.001 respectively). Participants who experienced mild AMS had lower end‐exercise RR at 3500 m (19.2 vs. 21.3, p  = 0.017). In a multi‐variable regression model, only lower end‐exercise SpO2 (OR 0.870, p  < 0.001) and no previous exposure to altitude >5000 m (OR 2.740, p ‐value 0.003) predicted the development of moderate‐to‐severe AMS. The Xtreme Everest Step‐Test offers a simple, reproducible field test to help predict AMS, albeit with relatively limited predictive precision. Abstract : We evaluated the performance of a simple exercise challenge at altitude (the Xtreme Everest Step‐Test) in predicting acute mountain sickness (AMS) on a trek to Everest Base Camp (5300 m). The overall occurrence of AMS during the trek was high (73.5%). Lower peripheral oxygen saturation (SpO2 ) following the Xtreme Everest Step‐Test at 3500 m and no previous exposure to altitude >5000 m predicted the development of moderate to severe AMS (Lake Louise score ≥5) during the trek. The Xtreme Everest Step‐Test offers a simple, reproducible field test to contribute towards the prediction of AMS, albeit with relatively limited predictive precision.